The Effect of Wordwall Digital Games on Students’ Vocabulary Achievement at Grade V of SD Negeri 4 Padangkerta - Lita, Ni Ketut Paula; Budiarta, Luh Gd Rahayu; Dambayana, Putu Eka (IJLHE: International Journal of Language, Humanities, and Education, 2026)
The purpose of this study was to see whether the use of the Wordwall digital games as a learning medium had a significant effect on the vocabulary achievement of V-grade students at SD Negeri 4 Padangkerta. This study employed a quantitative approach using a quasi-experimental with a post-test only design. The participants of this study were fifth-grade students from the experimental and control groups with a total sample of 68 students. Data was collected through a post-test and analyzed using the SPSS 26.0 program. Based on the descriptive statistical analysis, the results showed that the experimental group achieved a higher mean score (M = 88.82) than the control group (M = 52.56). Furthermore, the results of the Mann–Whitney U test showed a significant difference between the experimental group and the control group (Sig. (2-tailed) = 0.000, p < 0.05), with a large effect size (r = 0.87), indicating that the treatment had a meaningful effect on students' vocabulary achievement. Therefore, the alternative hypothesis (Hₐ) was accepted, and the null hypothesis (H₀) was rejected. These findings imply that the use of Wordwall digital games as a technology-based learning can be an effective learning medium to support vocabulary development and enhance student engagement in English learning at the elementary school level.